The VicRK System of Streptococcus mutans Responds to Oxidative Stress - Deng, D.M.; Liu, M.J.; ten Cate, J.M.; Crielaard, W. (Journal of dental research, 2007)
In Streptococcus mutans, virulence and cariogenicity may be modulated via the two-component regulatory system VicRK. Environmental signals, sensed by VicK, inducing this modulation are still unclear, however, and were investigated in the present study. We found that VicRK displays homology with protein-domains that, in other bacteria, are involved in redox-sensing. After constructing a VicRK-promoter GFP-reporter strain, we showed increased fluorescence intensity under oxidative stress. Potential interference of alternative signals and experimental conditions on GFP expression was excluded by the use of negative and positive control strains. Finally, we constructed a clean vicK knockout mutant, which proved to be more sensitive to H2O2 than the wild-type. In conclusion, this study showed that the VicRK system responds to and protects against oxidative stress. As a result, a link between oxidative/redox stress and the cariogenic nature of S. mutans can be hypothesized.